Research on the Decompression Effects of Shaft Explosion-Proof Door at Different Lifting Heights - Xue-Bo Zhang; Shuai-Shuai Shen; Zhi-Yang Gao; Ming Yang; Jing-Zhang Ren (Shock and Vibration)
To study the decompression effects of shaft explosion-proof door at different lifting heights, this paper designed the gas explosion testing system. Based on the test results, this paper made a numeric analysis of the change regularities of the shock wave overpressure when the shaft explosion-proof door was lifted at different heights. Finally, this paper determined the proper lifting height of the shaft explosion-proof door and put forward the active decompression concept. The research showed that (1) the shock wave overpressure at the explosion-proof door decreased in a power exponential relationship as the lifting height increased. When the lifting height increased from 0 cm to 5 cm, the peak overpressure at the explosion-proof door decreased from 36.06 kPa to 22.47 kPa, dropping by 37.7%. When it was lifted at a height of 40 cm, the overpressure dropped to 11.20 kPa and the decompression reached 68.9%. (2) The overpressure at the ventilator decreased in a power exponential relationship as the lifting height increased. When the lifting height of the explosion-proof door increased from 0 cm to 5 cm, the decompression ratio reached the maximum 18.4%. After that, the decompression effect became worse and worse. (3) The explosion-proof door could depressurize and protect the ventilator at gas explosion but with limited effects. To protect the ventilator and the explosion-proof door to the maximum, it was suggested that the pressure sensor was set up somewhere in the mine where the gas explosion is likely to occur. In this way, the explosion was sensed in time and the explosion-proof door could be actively lifted for decompression. This paper was of great guiding significance in optimizing the design of the explosion-proof door equipment, reducing the loss of gas explosion accidents as well as carrying out the emergency rescue.